(untitled) (Research, Society and Development, 2022)
During the aging process results from physiological changes in the nervous and endocrine system that propitiate the onset of insomnia, it is estimated that sleep disorders affect around 50% of the elderly. The first-line treatment for insomnia are benzodiazepines, this class should be avoided by the elderly because they increase the risk of fall. This study is a systematic bibliographic review of quantitative nature, which used the pubmed, scientific electronic library online (SciELO) and Google Scholar platforms as a database for the research of scientific articles, published between 2016 and 2021, in Portuguese and English. Of the 200 results obtained, 189 were excluded, leaving only 11 articles. Among the articles analyzed, it was observed that even if contraindicated for this age group, the rate of benzodiazepine use by the elderly in Brazil is still high, and its main indication is currently the control of insomnia. In addition, there were strong indications of a relationship between prolonged bzd use and the development of dementia in the long term. As there is knowledge of side effects by the medical population, this should instruct patients on the risks and avoid iatrogenic.